THE EFFECT OF PROJECT-BASED LEARNING MODELS ON STUDENT MOTIVATION AND LEARNING OUTCOMES - Capah, Doris Yunidar; Mirza, Ade; Asep Nursangaji; Edy Yusmin; Revi Lestari Pasaribu; Agung Hartoyo (Jurnal Ilmu Pendidikan Indonesia, 2025)
Abstract: This study was conducted at SMP Negeri 2 Pontianak to test the effect of project-basedlearning (PjBL) on students' motivation levels and learning outcomes, and to understand the extent towhich perceptions of mathematics learning are related to motivation and learning outcomes. The methodused was an experiment with a posttest-only control design. The analysis showed that applying the PjBLmodel significantly affected learning motivation (sig value = 0.045) and learning outcomes (sig value =0.000). In addition, there was a significant positive relationship between students' perceptions ofmathematics learning and their motivation to learn (sig value = 0.000), although the relationship was notfound with learning outcomes (sig value = 0.933). Overall, the interaction between students' perceptionsand motivation on learning outcomes did not show a significant effect (sig value = 0.358). Therefore, itcan be concluded that the use of the project-based learning model is effective in improving student’smotivation and learning outcomes.Keywords: Project-based learning, motivation, learning outcomes